PELATIHAN ANALISIS KORELASI DAN REGRESI DENGAN MENGGUNAKAN PERANGKAT LUNAK “R” UNTUK MENINGKATKAN KETERAMPILAN PENGOLAHAN DATA BAGI GURU - Puspa, Sofia Debi; Joko Riyono; Fani Puspitasari; Christina Eni Pujiastuti (Jurnal Abdi Masyarakat Indonesia (JAMIN), 2024)
Regression analysis is a statistical method that aims to determine the relationship between one or more independent variables and the dependent variable. Correlation expresses the degree of linear relationship between the two variables. The application of regression and correlation analysis is needed, especially for teachers, to determine what factors influence students' understanding of learning and it can be seen how strongly a variable influences other variables. This Community Service Activity is motivated by the need for educators to analyze the causes of factors that influence students's understanding of learning through data. This Community Service for partners aims to provide understanding related to Correlation and regression Analysis with" R" software. It is hoped that this Community service will make it easier for educators to decide on suitable learning models in class after knowing what factors influence student understanding in learning. Fifty-one participants attended this activity, and the training was carried out online. Based on the comparison of pre-test and post-test scores, there is an increased understanding of Correlation and Regression Analysis. The average increase in the trainees' ability was 34.14, 83.67% of the average before the training.